Adjuvant Anti-HER2 Therapy, Treatment-Related Amenorrhea, and Survival in Premenopausal HER2-Positive Early Breast Cancer Patients. (5th June 2018) - Lambertini, Matteo; Campbell, Christine; Bines, José; Korde, Larissa A; Izquierdo, Miguel; Fumagalli, Debora; Del Mastro, Lucia; Ignatiadis, Michail; Pritchard, Kathleen; Wolff, Antonio C; Jackisch, Christian; Lang, Istvan; et al.
Abstract: Background: In premenopausal patients with human epidermal growth factor receptor 2 (HER2)–positive early breast cancer, the gonadotoxicity of trastuzumab and lapatinib remains largely uncertain, and the prognostic effect of treatment-related amenorrhea (TRA) is unknown. Methods: In the Adjuvant Lapatinib and/or Trastuzumab Treatment Optimization (BIG 2-06) phase III trial, HER2-positive early breast cancer patients were randomized (1:1:1:1) to receive one year of trastuzumab, lapatinib, their sequence, or their combination. As per study protocol, menopausal status was collected in all patients at random assignment and at week 37 visit. We investigated TRA rates and whether TRA in patients with hormone receptor–positive and –negative tumors would impact disease-free survival (DFS) and overall survival (OS). Landmark and time-dependent modeling were used to account for guarantee-time bias. All statistical tests were two-sided. Results: A total of 2862 premenopausal women were included, of whom 1679 (58.7%) had hormone receptor–positive disease. Median age was 43 (interquartile range = 38–47) years. Similar TRA rates were observed in the trastuzumab (72.6%), lapatinib (74.0%), trastuzumab→lapatinib (72.1%), and trastuzumab+lapatinib (74.8%) arms ( P = .64). The association between TRA and survival outcomes differed according to hormone-receptor status ( P interaction for DFS = .007; P interaction for OS = .003). For hormone receptor–positive patients, the TRA cohort had statistically significantly better DFS (adjusted hazard ratio [aHR] = 0.58, 95% confidence interval [CI] = 0.45 to 0.76) and OS (aHR = 0.63, 95% CI = 0.40 to 0.99) than the no TRA cohort. No difference was observed in hormone receptor–negative patients. Conclusions: In this unplanned analysis, no association between TRA rate and type of anti-HER2 treatment was observed. TRA was associated with statistically significant survival benefits in premenopausal hormone receptor–positive/HER2-positive early breast cancer patients.